Volume Scanning Electron Microscopy and Stereology for Investigation of SARS-CoV-2 Infected Murine Lung Tissues - Hatmanstorfer, Andrea (Jihočeská univerzita, 2023)
Investigation of the ultrastructural change in lungs upon infection with the alpha variant of the SARS-CoV-2 virus for a certain time. The lung tissue was imaged via serial block-face electron microscopy and quantified using stereology.
Volume Scanning Electron Microscopy and Stereology for Investigation of SARS-CoV-2 Infected Murine Lung Tissues
Keywords: Volume microscopy; Electron microscopy; Serial block-face electron microscopy; SARS-CoV-2; Stereology; Volume microscopy; Electron microscopy; Serial block-face electron microscopy; SARS-CoV-2; Stereology